Hydrogen production using economical and environmental friendly nanoparticulate hydroxyapatite and its ion doping - Kasidid Yaemsunthorn (2018)
© 2016 Hydrogen Energy Publications LLC Hydrogen production may be achieved using hydroxyapatite (HA) and ion-doped HA, economical and environmentally photocatalysts. HAs with a new minor absorption peak related to the increased photoactivity were discovered. Nanostructural characteristics of synthesized nanocrystalline hydroxyapatite were investigated. Ti 4+ cation incorporation and Zn 2+ , F − co-substituted HA were also produced and evaluated. Particle sizes of approximately 10–30 nm with considerably large surface area were obtained after heat treatment. HA shows moderate efficiency, having a 27.6 μmol h −1  g −1 hydrogen production rate under UV radiation, probably because of the minor peak at approximately 375 nm. However, the hydrogen production rate of the Ti 4+ -incorporated sample increased by a factor of 2.6, 72.3 μmol h −1  g −1